The hidden threat of retained rubber and radiolucent foreign bodies in extremity trauma: Diagnostic and surgical challenges - Doodati, Spandhana; Sultana, Reshmi; sahoo, samarth; ramavath, krishna; Reddy D, Venkateshwar (Journal of the Foot & Ankle, 2025)
Penetrating extremity injuries are common among individuals involved in farming and ground-level occupations, often caused by materials such as thorns, wood, ceramics, plastic, and metal. While foreign body retention is well-documented, retained rubber fragments are rarely reported. Such foreign bodies can trigger a granulomatous inflammatory response, leading to symptoms ranging from acute pain and swelling to chronic complications, such as abscesses and discharging sinuses, if untreated. Radiological imaging is key to diagnosis. While plain radiographs detect radiopaque objects, they often miss radiolucent materials such as rubber, wood, and plastic. Ultrasound and magnetic resonance imaging are more effective in these cases, with the latter offering superior sensitivity and aiding in surgical planning. Surgical removal is the definitive treatment, but radiolucent materials pose intraoperative challenges, as C-arm imaging is ineffective. Ultrasound-guided extraction enhances precision, particularly for deeply embedded foreign bodies. In our case, despite initial challenges, intraoperative ultrasound guidance and meticulous dissection ensured successful removal, highlighting the importance of advanced imaging and surgical expertise in managing complex foreign body injuries. Level of evidence V; Case report.